Pendidikan Kitab Kuning: Jalan Menuju Karakter Moderat dan Menghadang Radikalisme - Taubah, Miftachul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
Studying the yellow books is the key to counteracting radicalism and shaping a moderate character in Islamic religious education. Using a qualitative integrative review approach, the author integrates and summarizes the education of the yellow books with a moderate attitude to ultimately counteract radicalism. The yellow books contain profound principles of Islam, allowing a strong understanding of the true and authentic teachings of Islam, preventing radical interpretations. Learning the yellow books also opens the door to diverse thinking, promoting tolerance, and fostering good ethics in daily life. The importance of understanding the yellow books in addressing radicalism and extremism also impacts scholars and religious leaders who promote peace and moderation. Additionally, the study of the yellow books assists the younger generation in facing contemporary issues. However, if the yellow books are not preserved, there is a risk of losing the valuable intellectual heritage of Islam, intellectual skills, declining interfaith dialogue capabilities, cultural identity loss, religious education regression, and an inability to confront contemporary challenges